PERFORMANCE OF REGIONAL CIVIL SERVICE AGENCY EMPLOYEES IN PALU CITY - Filo Leonardo Tinggogoy; Fachrul Reza; Rusmawaty BTE Rusdin (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study was conducted at the Office of the Regional Civil Service Agency of Palu. In this study, the researchers applied the concept proposed by Agus Dwiyanto concerning five indicators that determine the performance of government employees, namely productivity, responsiveness, accountability, service quality, and responsibility. This study was descriptive research with a qualitative approach. Informants were selected purposively, in which the researchers deliberately chose people who were considered to understand the investigated problem. The informants in this study were the Head of the Regional Civil Service Agency of Palu, the Head of the Division of Transfer and Rank, the Head of the Sub-Division of Rank, employees of the Regional Civil Service Agency of Palu, and three civil servants from other agencies. Results showed as follows. In terms of productivity, there are still employees who are late to come for work which can result in a lack of employee working hours from the work time that has been set. In terms of service quality, it has not been running well because there are often delays in making decrees concerning appointments to be civil servants. In terms of responsiveness, it has gone well. The government employees of the Regional Civil Service Agency of Palu provide solutions to the problems faced by civil servants in Palu regarding promotions. In terms of responsibility, it has run quite well, as shown by the presence of a suggestion box and telephone-based service for civil servants to submit their suggestions and criticisms. In terms of accountability, it has run well, as indicated by the conditions found, in which employees have completed their works and reports on time. In addition, they are also responsible for the results of their works and reports to their respective heads of division if an error is found in making reports or delays in collecting reports.